New linker installation in metal–organic frameworks. Issue 32 (1st August 2019) - Pang, Qingqing; Tu, Binbin; Li, Qiaowei
Abstract : Installation of new organic components (including multitopic anionic and neutral linkers) in MOFs and MOPs for multicomponent materials. Abstract : In this Frontier article, we provide a brief overview of recent progress in the new organic component installation in metal–organic frameworks (MOFs) by single-crystal to single-crystal transformation. We discuss the criteria for the MOFs which could provide accessible vacant sites for new linker installation. We highlight three different categories of linker installation based on the nature and the roles of the new linkers. The present challenges and future opportunities in this field are also discussed.